Developmental changes in myocardial B cells mirror changes in B cells associated with different organs - Cibele Rocha‐Resende; Wei Yang; Wenjun Li; Daniel Kreisel; Luigi Adamo; Douglas L. Mann (2020)
The naive heart harbors a population of intravascular B cells that make close contact with the cardiac microvasculature. However, the timing of their appearance and their organ specificity remain unknown. To address this knowledge gap, we performed a systematic analysis of B cells isolated from the myocardium and other organs, from embryonic life to adulthood. We found that the phenotype of myocardial B cells changed dynamically during development. While neonatal heart B cells were mostly CD11b+ and CD11b– CD21–CD23–, adult B cells were predominantly CD11b–CD21+CD23+. Histological analysis and intravital microscopy of lung and liver showed that organ-associated B cells in contact with the microvascular endothelium were not specific to the heart. Flow cytometric analysis of perfused hearts, livers, lungs, and spleen showed that the dynamic changes in B cell subpopulations observed in the heart during development mirrored changes observed in the other organs. Single cell RNA sequencing (scRNAseq) analysis of B cells showed that myocardial B cells were part of a larger population of organ-associated B cells that had a distinct transcriptional profile. These findings broaden our understanding of the biology of myocardial-associated B cells and suggest that current models of the dynamics of naive B cells during development are incomplete.